Microstructure and phase evolution of SrTiO3 thin films on Si prepared by the use of polymeric precursors - Zanetti, S. M.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Leite, E. R. (Elsevier, 1997)
The use of polymeric precursors was employed in preparing SrTiO3 thin films by dip coating using Si (111) as substrate. Crack free films were obtained after sintering at temperatures ranging from 550 to 1000°C. The microstructure, characterized by SEM, shows the development of dense polycrystalline films with smooth surface and mean grain size of 52 nm, for films sintered at 1000°C. Grazing incident angle XRD characterization of these films shows that the SrTiO3 phase crystallizes from an inorganic amorphous matrix. No intermediate crystalline phase was identified.
Keywords: Microstructure; Pechini technique; Si substrates; SrTiO3; Strontium carbonate; Thin films; Titanium citrate solutions; Ceramic materials; Coatings; Oxides; Sintering; Titanium compounds; X ray diffraction analysis; Ceramic films; Strontium titanate; Strontium compounds